2021
DOI: 10.1002/jcla.23905
|View full text |Cite
|
Sign up to set email alerts
|

Novel factor VII gene mutations in six families with hereditary coagulation factor VII deficiency

Abstract: Introduction Hereditary human coagulation factor VII (FVII) deficiency is an inherited autosomal recessive hemorrhagic disease involving mutations in the F7 gene. The sites and types of F7 mutations may influence the coagulation activities of plasma FVII (FVII: C) and severity of hemorrhage symptoms. However, the specific mutations that impact FVII activity are not completely known. Methods We tested the coagulation functions and plasma activities of FVII in seven patients recruited from six families with here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In 2021, Zhang et al detected four novel variations (c.251T>C, c.466G>A, c.1016C>T, c.-16T>G) and investigated their pathogenicity using PyMOL2.4, Swiss-PDB Viewer, SIFT, POLYPHEN-2. Bioinformatics analyses found these variations pathogenic (49). In another study, Liang et al detected two novel variations in three patients with FVII deficiency; the molecular model analysis of the two novel mutations (Cys115Arg and Pro324Leu) indicated impairment of the proper folding of the EGF1 domain and impairment of the F7 coagulant activity (50).…”
Section: F7 Gene Variationsmentioning
confidence: 99%
“…In 2021, Zhang et al detected four novel variations (c.251T>C, c.466G>A, c.1016C>T, c.-16T>G) and investigated their pathogenicity using PyMOL2.4, Swiss-PDB Viewer, SIFT, POLYPHEN-2. Bioinformatics analyses found these variations pathogenic (49). In another study, Liang et al detected two novel variations in three patients with FVII deficiency; the molecular model analysis of the two novel mutations (Cys115Arg and Pro324Leu) indicated impairment of the proper folding of the EGF1 domain and impairment of the F7 coagulant activity (50).…”
Section: F7 Gene Variationsmentioning
confidence: 99%
“…A complete blood count showed a white cell count of 2.9 × 10 9 /L, a hemoglobin level of 83 g/L and a platelet count of 212 × 10 9 /L. Routine coagulation tests showed that the prothrombin time (PT) was markedly elevated (35.0 s, normal range 10-14 s); the international normalized ratio (INR) was 2.92 (normal range [10][11][12][13][14]; the FVII activity level was extremely low at 2.1% of normal on a Siemens automatic blood coagulation analyzer (Siemens 5100); and the activated partial thromboplastin time (APTT), thrombin time (TT) and D-dimer were within their respective reference ranges. The FVII:Ag was checked with an enzyme-linked immunosorbent assay (ELISA) kit (Changfeng), the phenotypes of this family are shown in Table 1, and the pedigree is shown in Figure 1.…”
Section: A S E Pr E S E Ntati O Nmentioning
confidence: 99%
“…9 Phe84Ser and p.Gly156Cys affected the Gla and EGF domains of FVII, respectively, causing hereditary coagulation factor VII deficiency. 10 Here, we report a pedigree of congenital FVII deficiency, the proband was a 30-year-old female with severely low FVII activity who was subsequently diagnosed with congenital compound heterozygous FVII deficiency. The clinical manifestations and laboratory results of the proband and her family members are presented, the genetic analysis of the proband was performed by secondgeneration sequencing, and the bioinformatics and amino acid homology analyses were conducted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas FVII:C shows a poor correlation to severity of bleeding phenotype the type and the site of a F7 variant may be helpful to predict hemorrhagic risks (13). For example, mutations affecting TFPI-binding exosites of FVII may markedly prolong clotting time (14).…”
Section: Introductionmentioning
confidence: 99%